ANALISIS MANFAAT SISTEM PEMBELAJARAN MOVING CLASS TERHADAP MOTIVASI BELAJAR SISWA DI SMA ISLAM AS-SHOFA PEKANBARU - Fatlaini, Raudha; Gimin, Gimin; Hendripidies, Hendripidies (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the benefits of moving class learning systems on student motivation at As-Shofa Islamic High School Pekanbaru. The population in this study were teachers at As-Shofa Islamic High School Pekanbaru as many as 31 people, and the sample was 25 teachers each of the study fields, with sampling techniques using purposive sampling. Measurement of data using questionnaires and observations. Analysis of the data used is descriptive analysis and different tests using SPSS. The results of the descriptive research show the benefits of the moving class learning system on students' learning motivation at the singkron As-Shofa Islamic High School between descriptive analysis and Paired Sample T-test analysis, which is significant when the moving class is implemented and before the moving class. Where in the descriptive analysis the majority of the samples chose high and sufficient student motivation at the time before the moving class of 88%, as well as in the SPSS Paired Sample T-test, showed sig-2 (tailed) 0,000 <0,005 where there were significant differences in motivation student learning when moving class and before moving class. For this reason, Ha is rejected and Ho is accepted.Key Words: Benefits, Moving class, Learning Motivation